2013
DOI: 10.1182/blood-2012-12-474387
|View full text |Cite
|
Sign up to set email alerts
|

Clonal selection in xenografted TAM recapitulates the evolutionary process of myeloid leukemia in Down syndrome

Abstract: Key Points• Genetically heterogeneous subclones with varying leukemia-initiating potential exist in neonatal transient abnormal myelopoiesis.• This novel xenograft model of transient abnormal myelopoiesis may provide unique insight into the evolutionary process of leukemia.Transient abnormal myelopoiesis (TAM) is a clonal preleukemic disorder that progresses to myeloid leukemia of Down syndrome (ML-DS) through the accumulation of genetic alterations. To investigate the mechanism of leukemogenesis in this disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
1
22
0
1
Order By: Relevance
“…[9][10][11] In several cases, the same patient-specific GATA1-mutation was present in TMD and ML-DS, 12 implying a clonal evolution with the acquisition of additional mutations. 13 These observations argue that elimination of the preleukemic TMD clone would prevent the development of ML-DS.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In several cases, the same patient-specific GATA1-mutation was present in TMD and ML-DS, 12 implying a clonal evolution with the acquisition of additional mutations. 13 These observations argue that elimination of the preleukemic TMD clone would prevent the development of ML-DS.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that TAM xenograft models would be an attractive method for investigating the evolutionary process of leukemia. In contrast to a previous study in which TAM cells showed a limited ability to expand in immunodeficient mice [56], we established a xenograft model of TAM using NOD/Shi-scid, IL-2Rγnull (NOG) mice, which mimicked the progression of TAM to DS-AMKL [57]. The presence of the same GATA1 mutation was confirmed in the primary TAM cells and the engrafted cells in the NOG mice.…”
Section: Tam Xenograft Modelmentioning
confidence: 95%
“…2). Recent studies reveal that genetic intratumoral heterogeneity was evident not only in the ML-DS, but also in the TAM phase [57,62], and that ML-DS originated from one of the multiple subclones present in the TAM phase of the disease. NGS methodology also showed the precise frequency of GATA1 mutation in DS [40] and may be used in the future to make diagnostic and treatment decisions in DS-related myeloid disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors postulated that leukemia progression requires a "third-hit driver," putative driver mutations resulting in aberrant activation of WNT, JAK-STAT, or MAPK-PI3K pathways and consequent overexpression of MYC (Nikolaev et al 2013 ). The presence of multiple subclones with varying leukemia-initiating potential and selfrenewal capacity was also suggested in a xenograft model of TAM: during serial transplantation of TAM-derived cells, divergent subclones with another GATA1 mutation and various copy number alterations emerged (Saida et al 2013 ). Epigenetic changes can also contribute to leukemogenesis in DS.…”
Section: Gata1 Gene and Ds-acute Myeloid Leukemogenesismentioning
confidence: 97%